Red Fluorescent Probe for Monitoring the Dynamics of Cytoplasmic Calcium Ions1. Issue 14 (25th February 2013) - Egawa, Takahiro; Hirabayashi, Kazuhisa; Koide, Yuichiro; Kobayashi, Chiaki; Takahashi, Naoya; Mineno, Tomoko; Terai, Takuya; Ueno, Tasuku; Komatsu, Toru; Ikegaya, Yuji; Matsuki, Norio; Nagano, Tetsuo; et al.
<x xml:space="preserve">Abstract</x> We see red (and yellow and green): Probe 1 was developed for the visualization of cytoplasmic Ca2+, a pivotal second messenger in many biological responses. The new probe is suitable for multicolor imaging for the simultaneous detection of metal ions or proteins and is superior to the existing red fluorescent probe Rhod‐2 for the monitoring of cytoplasmic Ca2+ oscillation in cultured cells (see fluorescence images of cells with 1 (top) and Rhod‐2 (bottom)).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>